Nutritional Content Identification of Local-Based Foods for Pregnant Mothers' Nutritional Needs - Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitriani Fitriani; Rahayu Indriasari; Veni Nella Syahputri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Pregnant women with chronic energy deficiency (CED) are likely to have an increased risk of fetal death (stillbirths), premature birth, congenital disabilities, low birth weight infants (LBW), and infant mortality. CED also contributes to approximately 40% of stunting incidents in Indonesia. This study aimed to identify the nutritional content of local-based food consumed by pregnant women. This research was carried out in 3 stages; first, a descriptive approach to analyze the nutritional content of local foods. Second, a quasi-experiment was conducted to see the effect of local food consumption. Third, a qualitative approach to explore food consumption patterns was also be conducted. The results showed that the type of local Acehnese was wet food containing high energy, water, minerals, protein, fat and carbohydrates. This food can be used as an alternative for pregnant women to support their nutritional requirements. The present study also found a significant change in mid-upper arm circumference and weight gain of pregnant women after consuming wet food. Overall, the staple foods often consumed are rice, cassava and Indomie instant noodle because they are accessible and affordable for pregnant women and their families. The Acehnese local wet food can be used as a complementary food for pregnant women. Inappropriate consumption patterns can increase the risk of nutritional deficiencies among pregnant women, which will have short-term and long-term consequences on health. Abstrak: Ibu hamil dengan kekurangan energi kronis (KEK) cenderung memiliki peningkatan risiko kematian janin (lahir mati), kelahiran prematur, cacat bawaan, bayi berat lahir rendah (BBLR), kematian bayi. KEK juga berkontribusi terhadap sekitar 40% kejadian stunting di Indonesia. Penelitian ini bertujuan untuk mengidentifikasi kandungan gizi pangan berbasis lokal yang dikonsumsi ibu hamil. Penelitian ini dilakukan dalam 3 tahap; pertama, pendekatan deskriptif untuk menganalisis kandungan gizi pangan lokal. Kedua, kuasi eksperimen dilakukan untuk melihat pengaruh konsumsi pangan lokal. Ketiga, pendekatan kualitatif untuk menggali pola konsumsi pangan juga dilakukan. Hasil penelitian menunjukkan bahwa jenis makanan lokal Aceh adalah makanan basah yang mengandung energi tinggi, air, mineral, protein, lemak dan karbohidrat. Makanan ini dapat dijadikan sebagai alternatif ibu hamil dalam menunjang kebutuhan gizinya. Penelitian ini juga menemukan perubahan signifikan pada lingkar lengan atas dan penambahan berat badan ibu hamil setelah mengonsumsi makanan basah. Secara keseluruhan, makanan pokok yang sering dikonsumsi adalah nasi, singkong dan mie instan Indomie karena makanan ini mudah didapat dan terjangkau oleh ibu hamil dan keluarganya. Makanan basah khas Aceh ini bisa dijadikan makanan pendamping ibu hamil. Pola konsumsi yang tidak tepat dapat meningkatkan risiko kekurangan gizi pada ibu hamil yang akan berdampak jangka pendek dan jangka panjang terhadap kesehatan.